High-purity corundum refractory brick and manufacturing process thereof

The combination of aluminum sol and plate-shaped corundum aggregates and other components is prepared by the sol-gel method, which solves the problems of high-temperature performance and low production efficiency of traditional refractory bricks, and achieves high-performance refractory bricks at lower sintering temperatures, reducing the number of refractory bricks The impact of energy consumption and impurities introduced by clay are caused.

CN119285336AInactive Publication Date: 2025-01-10ZIBO REFRATECHNIK REFRACTORIES CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411823060.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional high-purity corundum refractory bricks require ultra-high firing temperature, resulting in waste of energy and low production efficiency, and the introduction of clay will affect its high-temperature performance.

Method used

The nano-grade aluminum sol is prepared by sol-gel method, combining plate-shaped corundum aggregate, boron oxide, aluminum hydroxide and whisker growth promoter, and replacing traditional clay as a binding agent through low-temperature baking and sintering treatment to reduce the sintering temperature And improve the high-temperature mechanical properties of refractory bricks.

Benefits of technology

The indicators that are higher than those of traditional clay combined with refractory bricks are achieved at a lower sintering temperature (1420~1480°C), which improves the purity and high-temperature usage performance of refractory bricks, saves energy and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285336A_ABST
    Figure CN119285336A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of refractory brick manufacturing, and discloses a high-purity corundum refractory brick and a manufacturing process thereof. The refractory brick is prepared by mixing the following components: tabular corundum aggregate, boric oxide, aluminum hydroxide, a whisker growth promoter and alumina sol according to a ratio of (5-15): (1-5): (0.5-2): 1: (2-6). The manufacturing process comprises the following steps: S1, preparing aluminum sol; s2, providing tabular corundum aggregate; s3, adding boric oxide, aluminum hydroxide and a whisker growth promoter into the aluminum sol to obtain a mixture; s4, adding tabular corundum aggregate into the mixture to obtain a brick material; s5, feeding the brick material into a mold, pressing and baking, and demolding to obtain a green brick; s6, sintering the green brick to obtain the refractory brick. The firing temperature of the high-purity corundum refractory brick can be reduced, and the purity and high-temperature use performance of the refractory brick can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory brick production, in particular to a high-purity corundum refractory brick and a production process of the refractory brick. Background Art

[0002] At present, industrial high-temperature kilns have increasingly stringent requirements on the high-temperature mechanical properties of refractory materials, especially for high-purity corundum systems, which are increasingly widely used, covering high-temperature areas of various industrial kilns such as steel, cement, non-ferrous metals, and waste incineration. However, since traditional high-purity corundum refractory bricks require ultra-high firing temperatures, this not only wastes energy, but also limits their production efficiency and quantity. In addition, traditionally, clay is used to produce high-purity corundum refractory bricks. The introduction of clay is an impurity for high-purity corundum refractory bricks, which will have an adverse effect on their high-temperature use. Summary of the invention

[0003] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a high-purity corundum refractory brick and its production process to save energy, further improve the high-temperature mechanical properties of the refractory brick itself, and effectively improve the production efficiency of refractory bricks.

[0004] A high-purity corundum refractory brick comprises the following components: plate-shaped corundum aggregate, boron oxide, aluminum hydroxide, a whisker growth promoter and aluminum sol are mixed in a ratio of 5-15:1-5:0.5-2:1:2-6 to obtain the refractory brick.

[0005] As a further improvement of the above solution, the plate-shaped corundum aggregate is a dense crystal with a flaky microscopic crystal phase, and the plate-shaped corundum aggregate is made of alumina.

[0006] As a further improvement of the above solution, the whisker growth promoter is at least one of cobalt powder, nickel powder, copper powder and titanium powder.

[0007] As a further improvement of the above scheme, the refractory bricks are composed of the following by weight: 30% to 70% plate-shaped corundum aggregate, 5% to 20% boron oxide, 5% to 10% aluminum hydroxide, 5% to 8% whisker growth promoter, and 10% to 30% aluminum sol.

[0008] As a further improvement of the above scheme, the refractory bricks are composed of the following by weight: 60% plate-shaped corundum aggregate, 7% boron oxide, 6% aluminum hydroxide, 5% whisker growth promoter, and 22% aluminum sol.

[0009] A refractory brick manufacturing process, which is used to manufacture the high-purity corundum refractory brick, comprises the following steps: S1 Preparation of aluminum sol by sol-gel method; S2 provides plate-shaped corundum aggregate; S3. Add boron oxide, aluminum hydroxide and a whisker growth promoter to the aluminum sol, stir and mix, and let stand for 2 to 5 hours to obtain a mixture; S4 adding plate-shaped corundum aggregate to the mixed material, stirring and mixing to obtain a brick material; S5 sends the brick material into the mold, presses and bakes it, and then demoulds it to obtain the brick blank; S6 puts the bricks into a brick kiln for sintering to obtain refractory bricks.

[0010] As a further improvement of the above scheme, the sol-gel method is used to prepare aluminum sol, and the specific operation process is as follows: S11: dissolving polyvinyl pyrrolidone in distilled water to prepare an aqueous phase for later use; S12: dissolving the ground aluminum isopropoxide in isopropanol in a certain proportion to form an aluminum alcoholate phase; S13 ultrasonically treats the aluminum alcohol phase for 20-30 min to obtain a suspension; S14: dripping the suspension into the aqueous phase, stirring and hydrolyzing completely, then dripping nitric acid and stirring to obtain aluminum sol.

[0011] As a further improvement of the above scheme, the aluminum sol is hydrated aluminum oxide, which forms chain-like fibers during the gel process. In the present invention, the nano-scale aluminum sol is prepared by the sol-gel method, and based on the chain-like fiber structure, the aluminum sol is endowed with a high-strength binding effect, thereby replacing the traditional method of using clay as a binder to produce refractory bricks.

[0012] As a further improvement of the above scheme, pure alumina is taken, ground, formed and dried, and then placed in a vertical kiln and rapidly heated to 1900~2000℃ for sintering, and then cooled to form dense crystals. The crystals are crushed and ball-milled to obtain plate-shaped corundum aggregate with a particle size of 2~10mm.

[0013] As a further improvement of the above scheme, during the pressing and baking process, the pressing pressure is 115-200 MPa‌ and the baking temperature is 75-85° C. The present invention is based on compacting the brick material by pressing, and then curing the brick material by low-temperature baking to facilitate demoulding.

[0014] As a further improvement of the above scheme, the sintering process is carried out in a kiln, the sintering temperature is 1420-1480°C, and the sintering time is 20-30h. The present invention uses alumina sol to replace traditional clay to play a bonding role, which overcomes the problem that the introduction of clay leads to the presence of impurities in refractory bricks, reduces the purity of the sintered finished product and affects the performance of the bricks. At the same time, alumina sol reduces the firing temperature of the bricks, so that the sintering temperature of 1420-1480°C can reach or even exceed the performance index of the refractory bricks produced by the traditional use of clay to make refractory bricks, which needs to be sintered at no less than 1600°C.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses alumina sol to replace traditional clay to play a binding role, thereby overcoming the problem that the introduction of clay leads to the presence of impurities in the refractory bricks, reduces the purity of the sintered product and affects the performance of the bricks. At the same time, alumina sol reduces the firing temperature of the bricks, so that the sintering temperature of 1420-1480°C can reach or even exceed the performance indicators of the refractory bricks produced by the traditional use of clay to make refractory bricks, which need to be sintered at not less than 1600°C.

[0016] The main component of the aluminum sol of the present invention is aluminum oxide, which is consistent with the material of the plate-shaped corundum aggregate used in refractory bricks. During sintering, the aluminum sol is completely transformed into α-Al2O3, which has a high melting point, high hardness, high wear resistance and high corrosion resistance, thereby further improving the purity and high-temperature performance of refractory bricks. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Shown is a flow chart of a manufacturing process of a refractory brick provided by the present invention. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. Additional aspects and advantages of the present invention will be given in part in the following description, and will become apparent from the following description, or will be understood through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.

[0019] The specific embodiments of the present invention are described in detail below. Example

[0020] This embodiment provides a high-purity corundum refractory brick, which is composed of the following by weight: 50% plate-shaped corundum aggregate, 15% boron oxide, 8% aluminum hydroxide, 7% cobalt powder, and 20% aluminum sol. The plate-shaped corundum aggregate is a dense crystal with a flaky microscopic crystal phase, and the plate-shaped corundum aggregate is made of aluminum oxide.

[0021] The manufacturing process of the high-purity corundum refractory bricks of this embodiment includes the following steps: S1 Aluminum sol was prepared by sol-gel method.

[0022] The sol-gel method is used to prepare aluminum sol, and the specific operation process is as follows: S11: Dissolve polyvinyl pyrrolidone in distilled water to prepare an aqueous phase for later use.

[0023] S12: Dissolve the finely ground aluminum isopropoxide in isopropanol in a certain proportion to form an aluminum alcohol phase.

[0024] S13: The aluminum alcohol phase is subjected to ultrasonic treatment for 20 min to obtain a suspension.

[0025] S14: dripping the suspension into the aqueous phase, stirring and hydrolyzing completely, then dripping nitric acid and stirring to obtain aluminum sol.

[0026] The alumina sol is hydrated alumina, which forms chain-like fibers during the gel process. In this embodiment, nano-scale alumina sol is prepared by the sol-gel method, and based on the chain-like fiber structure, the alumina sol is endowed with a high-strength binding effect, thereby replacing the traditional method of using clay as a binder to produce refractory bricks.

[0027] S2 takes pure alumina, grinds it, shapes it, and dries it, then places it in a vertical kiln and rapidly heats it to 1900°C for sintering, and then cools it to form dense crystals. After the crystals are crushed, ball-milled, and sieved, plate-shaped corundum aggregate with a particle size of 2 mm is obtained.

[0028] S3: Add boron oxide, aluminum hydroxide and cobalt powder to the aluminum sol, stir and mix, and let stand for 2 hours to obtain a mixed product. The mixing temperature is 100°C.

[0029] In this embodiment, boron oxide and aluminum hydroxide are added to the aluminum sol, and the boron oxide and aluminum hydroxide are used as whisker binding materials, and the following reaction occurs: 9Al2O3(s) + 2B2O3(l) = 9Al2O3·2B2O3; 2Al(OH)3(s) = Al2O3(s) + 3H2O(g); In this embodiment, in the sol system, B2O3 is transported to the vicinity of Al2O3, so that Al2O3·B2O3 whiskers are formed on the fibers in the aluminum sol, thereby further improving the mechanical strength of the produced refractory bricks.

[0030] S4: adding plate-shaped corundum aggregate to the mixed material, stirring and mixing to obtain brick material.

[0031] S5: putting the bricks into the mold, pressing and baking, and demolding to obtain the bricks, the pressing pressure is 115 MPa, and the baking temperature is 75° C. In this embodiment, the bricks are compacted by pressing, and then the bricks are solidified by low-temperature baking to facilitate demolding.

[0032] S6: placing the bricks into a brick kiln for sintering to obtain refractory bricks. The sintering is carried out in a kiln at a sintering temperature of 1420° C. and a sintering time of 20 hours.

[0033] In this embodiment, alumina sol is used to replace traditional clay to play a binding role, thereby overcoming the problem that the introduction of clay leads to the presence of impurities in the refractory bricks, reduces the purity of the sintered product and affects the performance of the bricks. At the same time, alumina sol reduces the firing temperature of the bricks, so that the sintering temperature of 1420~1480°C can reach or even exceed the performance indicators of refractory bricks made by traditional clay bonding, which requires sintering at not less than 1600°C. Example

[0034] This embodiment provides a high-purity corundum refractory brick, which has the following composition by weight: 60% plate-shaped corundum aggregate, 7% boron oxide, 6% aluminum hydroxide, 5% nickel powder, and 22% aluminum sol. The plate-shaped corundum aggregate is a dense crystal with a flaky microscopic crystal phase, and the plate-shaped corundum aggregate is made of aluminum oxide.

[0035] The manufacturing process of the high-purity corundum refractory bricks of this embodiment includes the following steps: S1 Aluminum sol was prepared by sol-gel method.

[0036] The sol-gel method is used to prepare aluminum sol, and the specific operation process is as follows: S11: Dissolve polyvinyl pyrrolidone in distilled water to prepare an aqueous phase for later use.

[0037] S12: Dissolve the finely ground aluminum isopropoxide in isopropanol in a certain proportion to form an aluminum alcohol phase.

[0038] S13: The aluminum alcohol phase is subjected to ultrasonic treatment for 24 min to obtain a suspension.

[0039] S14: dripping the suspension into the aqueous phase, stirring and hydrolyzing completely, then dripping nitric acid and stirring to obtain aluminum sol.

[0040] The alumina sol is hydrated alumina, which forms chain-like fibers during the gel process. In this embodiment, nano-scale alumina sol is prepared by the sol-gel method, and based on the chain-like fiber structure, the alumina sol is endowed with a high-strength binding effect, thereby replacing the traditional method of using clay as a binder to produce refractory bricks.

[0041] S2 takes pure alumina, grinds it, shapes it, and dries it, then places it in a vertical kiln and rapidly heats it to 1950°C for sintering, and then cools it to form dense crystals. After the crystals are crushed, ball-milled, and sieved, plate-shaped corundum aggregate with a particle size of 6 mm is obtained.

[0042] S3: Add boron oxide, aluminum hydroxide and nickel powder to the aluminum sol, stir and mix, and let stand for 3 hours to obtain a mixed material. The mixing temperature is 100°C.

[0043] In this embodiment, boron oxide and aluminum hydroxide are added to the aluminum sol, and the boron oxide and aluminum hydroxide are used as whisker binding materials, and the following reaction occurs: 9Al2O3(s) + 2B2O3(l) = 9Al2O3·2B2O3; 2Al(OH)3(s) = Al2O3(s) + 3H2O(g); In this embodiment, in the sol system, B2O3 is transported to the vicinity of Al2O3, so that Al2O3·B2O3 whiskers are formed on the fibers in the aluminum sol, thereby further improving the mechanical strength of the produced refractory bricks.

[0044] S4: adding plate-shaped corundum aggregate to the mixed material, stirring and mixing to obtain brick material.

[0045] S5: putting the bricks into the mold, pressing and baking, and demolding to obtain the bricks, the pressing pressure is 130 MPa, and the baking temperature is 80° C. In this embodiment, the bricks are compacted by pressing, and then the bricks are solidified by low-temperature baking to facilitate demolding.

[0046] S6: placing the bricks into a brick kiln for sintering to obtain refractory bricks. The sintering is carried out in a kiln at a sintering temperature of 1440° C. and a sintering time of 25 hours.

[0047] In this embodiment, alumina sol is used to replace traditional clay to play a binding role, thereby overcoming the problem that the introduction of clay leads to the presence of impurities in the refractory bricks, reduces the purity of the sintered product and affects the performance of the bricks. At the same time, alumina sol reduces the firing temperature of the bricks, so that the sintering temperature of 1420~1480°C can reach or even exceed the performance indicators of refractory bricks made by traditional clay bonding, which requires sintering at not less than 1600°C. Example

[0048] This embodiment provides a high-purity corundum refractory brick, which has the following composition by weight: 55% plate-shaped corundum aggregate, 12% boron oxide, 9% aluminum hydroxide, 6% copper powder, and 18% aluminum sol. The plate-shaped corundum aggregate is a dense crystal with a flaky microscopic crystal phase, and the plate-shaped corundum aggregate is made of aluminum oxide.

[0049] The manufacturing process of the high-purity corundum refractory bricks of this embodiment includes the following steps: S1 Aluminum sol was prepared by sol-gel method.

[0050] The sol-gel method is used to prepare aluminum sol, and the specific operation process is as follows: S11: Dissolve polyvinyl pyrrolidone in distilled water to prepare an aqueous phase for later use.

[0051] S12: Dissolve the finely ground aluminum isopropoxide in isopropanol in a certain proportion to form an aluminum alcohol phase.

[0052] S13: The aluminum alcohol phase is subjected to ultrasonic treatment for 28 min to obtain a suspension.

[0053] S14: dripping the suspension into the aqueous phase, stirring and hydrolyzing completely, then dripping nitric acid and stirring to obtain aluminum sol.

[0054] The alumina sol is hydrated alumina, which forms chain-like fibers during the gel process. In this embodiment, nano-scale alumina sol is prepared by the sol-gel method, and based on the chain-like fiber structure, the alumina sol is endowed with a high-strength binding effect, thereby replacing the traditional method of using clay as a binder to produce refractory bricks.

[0055] S2 takes pure alumina, grinds it, shapes it, and dries it, then places it in a vertical kiln and rapidly heats it to 1980°C for sintering, and then cools it to form dense crystals. After the crystals are crushed, ball-milled, and sieved, plate-shaped corundum aggregate with a particle size of 8 mm is obtained.

[0056] S3: Add boron oxide, aluminum hydroxide and copper powder to the aluminum sol, stir and mix, and let stand for 4 hours to obtain a mixed material. The mixing temperature is 100°C.

[0057] In this embodiment, boron oxide and aluminum hydroxide are added to the aluminum sol, and the boron oxide and aluminum hydroxide are used as whisker binding materials, and the following reaction occurs: 9Al2O3(s) + 2B2O3(l) = 9Al2O3·2B2O3; 2Al(OH)3(s) = Al2O3(s) + 3H2O(g); In this embodiment, in the sol system, B2O3 is transported to the vicinity of Al2O3, so that Al2O3·B2O3 whiskers are formed on the fibers in the aluminum sol, thereby further improving the mechanical strength of the produced refractory bricks.

[0058] S4: adding plate-shaped corundum aggregate to the mixed material, stirring and mixing to obtain brick material.

[0059] S5: The brick material is put into the mold, pressed and baked, and then demolded to obtain a brick blank. The pressing pressure is 150 MPa‌ and the baking temperature is 83° C. In this embodiment, the brick material is compacted by pressing, and then the brick material is solidified by low-temperature baking to facilitate demolding.

[0060] S6: placing the bricks into a brick kiln for sintering to obtain refractory bricks. The sintering is carried out in a kiln at a sintering temperature of 1450° C. and a sintering time of 27 hours.

[0061] In this embodiment, alumina sol is used to replace traditional clay to play a binding role, thereby overcoming the problem that the introduction of clay leads to the presence of impurities in the refractory bricks, reduces the purity of the sintered product and affects the performance of the bricks. At the same time, alumina sol reduces the firing temperature of the bricks, so that the sintering temperature of 1420~1480°C can reach or even exceed the performance indicators of refractory bricks made by traditional clay bonding, which requires sintering at not less than 1600°C. Example

[0062] This embodiment provides a high-purity corundum refractory brick, which has the following composition by weight: 52% plate-shaped corundum aggregate, 10% boron oxide, 6% aluminum hydroxide, 8% titanium powder, and 24% aluminum sol. The plate-shaped corundum aggregate is a dense crystal with a flaky microscopic crystal phase, and the plate-shaped corundum aggregate is made of aluminum oxide.

[0063] The manufacturing process of the high-purity corundum refractory bricks of this embodiment includes the following steps: S1 Aluminum sol was prepared by sol-gel method.

[0064] The sol-gel method is used to prepare aluminum sol, and the specific operation process is as follows: S11: Dissolve polyvinyl pyrrolidone in distilled water to prepare an aqueous phase for later use.

[0065] S12: Dissolve the finely ground aluminum isopropoxide in isopropanol in a certain proportion to form an aluminum alcohol phase.

[0066] S13: The aluminum alcohol phase is subjected to ultrasonic treatment for 30 min to obtain a suspension.

[0067] S14: dripping the suspension into the aqueous phase, stirring and hydrolyzing completely, then dripping nitric acid and stirring to obtain aluminum sol.

[0068] The alumina sol is hydrated alumina, which forms chain-like fibers during the gel process. In this embodiment, nano-scale alumina sol is prepared by the sol-gel method, and based on the chain-like fiber structure, the alumina sol is endowed with a high-strength binding effect, thereby replacing the traditional method of using clay as a binder to produce refractory bricks.

[0069] S2 takes pure alumina, grinds it, shapes it, and dries it, then places it in a vertical kiln and rapidly heats it to 2000°C for sintering, and then cools it to form dense crystals. After the crystals are crushed, ball-milled, and sieved, plate-shaped corundum aggregate with a particle size of 10 mm is obtained.

[0070] S3: Add boron oxide, aluminum hydroxide and titanium powder to the aluminum sol, stir and mix, and let stand for 5 hours to obtain a mixed material. The mixing temperature is 100°C.

[0071] In this embodiment, boron oxide and aluminum hydroxide are added to the aluminum sol, and the boron oxide and aluminum hydroxide are used as whisker binding materials, and the following reaction occurs: 9Al2O3(s) + 2B2O3(l) = 9Al2O3·2B2O3; 2Al(OH)3(s) = Al2O3(s) + 3H2O(g); In this embodiment, in the sol system, B2O3 is transported to the vicinity of Al2O3, so that Al2O3·B2O3 whiskers are formed on the fibers in the aluminum sol, thereby further improving the mechanical strength of the produced refractory bricks.

[0072] S4: adding plate-shaped corundum aggregate to the mixed material, stirring and mixing to obtain brick material.

[0073] S5: The brick material is put into the mold, pressed and baked, and then demolded to obtain a brick blank. The pressing pressure is 200 MPa‌ and the baking temperature is 85° C. In this embodiment, the brick material is compacted by pressing, and then the brick material is solidified by low-temperature baking to facilitate demolding.

[0074] S6: placing the bricks into a brick kiln for sintering to obtain refractory bricks. The sintering is carried out in a kiln at a sintering temperature of 1480° C. and a sintering time of 30 hours.

[0075] In this embodiment, alumina sol is used to replace traditional clay to play a binding role, thereby overcoming the problem that the introduction of clay leads to the presence of impurities in the refractory bricks, reduces the purity of the sintered product and affects the performance of the bricks. At the same time, alumina sol reduces the firing temperature of the bricks, so that the sintering temperature of 1420~1480°C can reach or even exceed the performance indicators of refractory bricks made by traditional clay bonding, which requires sintering at not less than 1600°C.

[0076] The above embodiments are merely preferred implementations of the present invention. Any simple modification, amendment and substitution of the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.

Claims

1. A high-purity corundum refractory brick, characterized in that: The refractory bricks have the following components: plate-shaped corundum aggregate, boron oxide, aluminum hydroxide, whisker growth promoter and aluminum sol are mixed in a ratio of 5-15:1-5:0.5-2:1:2-6 to obtain the refractory bricks.

2. The high-purity corundum refractory brick according to claim 1, characterized in that: The plate-shaped corundum aggregate is a dense crystal with a flaky microscopic crystal phase, and the plate-shaped corundum aggregate is made of alumina.

3. The high-purity corundum refractory brick according to claim 2, characterized in that: The whisker growth promoter is at least one of cobalt powder, nickel powder, copper powder and titanium powder.

4. The high-purity corundum refractory brick according to claim 3, characterized in that: The refractory bricks are composed of the following by weight: 30% to 70% plate-shaped corundum aggregate, 5% to 20% boron oxide, 5% to 10% aluminum hydroxide, 5% to 8% whisker growth promoter, and 10% to 30% aluminum sol.

5. The high-purity corundum refractory brick according to claim 4, characterized in that: The refractory bricks are composed of 60% plate-shaped corundum aggregate, 7% boron oxide, 6% aluminum hydroxide, 5% whisker growth promoter, and 22% aluminum sol.

6. A process for producing refractory bricks, which is used to produce the high-purity corundum refractory bricks as claimed in any one of claims 1 to 5, characterized in that: The manufacturing process comprises the following steps: S1 Preparation of aluminum sol by sol-gel method; S2 provides plate-shaped corundum aggregate; S3. Add boron oxide, aluminum hydroxide and a whisker growth promoter to the aluminum sol, stir and mix, and let stand for 2 to 5 hours to obtain a mixture; S4 adding plate-shaped corundum aggregate to the mixed material, stirring and mixing to obtain a brick material; S5 sends the brick material into the mold, presses and bakes it, and then demoulds it to obtain the brick blank; S6 puts the bricks into a brick kiln for sintering to obtain refractory bricks.

7. The manufacturing process according to claim 6, characterized in that: The sol-gel method is used to prepare aluminum sol, and the specific operation process is as follows: S11: dissolving polyvinyl pyrrolidone in distilled water to prepare an aqueous phase for later use; S12: dissolving the ground aluminum isopropoxide in isopropanol in a certain proportion to form an aluminum alcoholate phase; S13 ultrasonically treats the aluminum alcohol phase for 20-30 min to obtain a suspension; S14: dripping the suspension into the aqueous phase, stirring and hydrolyzing completely, then dripping nitric acid and stirring to obtain aluminum sol.

8. The manufacturing process according to claim 7, characterized in that: The aluminum sol is hydrated aluminum oxide. It forms chain-like fibers during the gelation process.

9. The manufacturing process according to claim 8, characterized in that: Pure alumina is ground, formed and dried, then placed in a vertical kiln and rapidly heated to 1900~2000℃ for sintering, and then cooled to form dense crystals. The crystals are crushed, ball-milled and sieved to obtain plate-shaped corundum aggregate with a particle size of 2~10mm.

10. The manufacturing process according to claim 9, characterized in that: During the pressing and baking process, the pressing pressure is 115-200 MPa‌ and the baking temperature is 75-85°C; The sintering process is carried out in a kiln, the sintering temperature is 1420-1480° C., and the sintering time is 20-30 hours.

Citation Information

Patent Citations

  • Corundum fireproof coating

    CN104926332A

  • High-strength, high-purity and low-silicon corundum brick for petrochemical industry, and preparation method for corundum brick

    CN105399432A

  • In-situ aluminum borate crystal whisker enhanced CFB boiler high-strength wear-resistant plastic refractory

    CN107954733A

  • Novel low-loss protective material for rocket launching platform

    CN114105616A

  • Porous inorganic material and its production

    JP1998203879A